2022
DOI: 10.1002/nop2.1534
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experiences of frontline nurses during the first 6 months of the COVID‐19 pandemic: An integrated literature review

Abstract: Aim The aim of this study was to explore the experiences of frontline nurses caring for patients during the first 6 months of the COVID‐19 pandemic. Design The JBI manual for evidence synthesis and the PRISMA guidelines for reporting. Data sources CINAHL Complete, MEDLINE, PsycINFO (EBSCO) and Scopus (Elsevier). Review Methods The JBI Mixed Methods Data Extraction Tool following a Convergent Integrated Approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(247 reference statements)
0
3
0
Order By: Relevance
“…Nurses forced into a gatekeeping role they knew was harmful to patients and families clashed with their values of providing excellent palliative care. This resulted in moral distress, reducing coping capacity and/or resignation, and numerous studies support these findings (Jackson et al, 2022;Tye, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…Nurses forced into a gatekeeping role they knew was harmful to patients and families clashed with their values of providing excellent palliative care. This resulted in moral distress, reducing coping capacity and/or resignation, and numerous studies support these findings (Jackson et al, 2022;Tye, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…A comprehensive literature review was undertaken to demonstrate the impact of the first 6 months of the pandemic on frontline nurses. 10 Findings suggested that the frontline nurse population have experienced fear for their own safety and that of their loved ones, ethical and moral challenges in the face of prioritizing resources, injuries from the wearing of personal protective equipment (PPE), and negative effects of physical and mental exhaustion as a direct result of the pandemic. 10 Within a year of COVID-19 onset, emergency nurses expressed greater intent to leave the profession within 5 years.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Findings suggested that the frontline nurse population have experienced fear for their own safety and that of their loved ones, ethical and moral challenges in the face of prioritizing resources, injuries from the wearing of personal protective equipment (PPE), and negative effects of physical and mental exhaustion as a direct result of the pandemic. 10 Within a year of COVID-19 onset, emergency nurses expressed greater intent to leave the profession within 5 years. 11 Typically, the emergency department is renowned for high and complex workloads within a very dynamic environment, all exacerbated in the face of the pandemic and creating a tipping point for many nurses who sought to leave the profession.…”
Section: Introductionmentioning
confidence: 99%